The Mediating Effect of Positive Illness Cognitions on Experiential Avoidance and Quality of Life in Breast Cancer Patients - Jing Han; Li Zhang; Yao Zhang; Ruijin Tang (Elsevier, 2021)
Objective: Illness cognition plays an essential role during physical, psychological, and social adjustment among patients with cancer. The present study aims to explore the mediating effects of positive illness cognition on experiential avoidance and quality of life (QOL) in this population. Methods: Between August 2017 and June 2019, we recruited 312 patients with breast cancer in the treatment period from a general tertiary hospital's breast department using convenience sampling. We used the Illness Cognition Questionnaire, the Acceptance and Action Questionnaire II, and the Functional Assessment of Cancer Therapy-Breast Scale. Results: The mean score of QOL was 93.39 (SD: 18.60) for patients with breast cancer. Positive illness cognition was closely related to the QOL and experiential avoidance. Experiential avoidance significantly negatively correlated with QOL (r = −0.59, P < 0.01) and positive illness cognition (r = −0.60, P < 0.01), while positive illness cognition significantly positively correlated with QOL (r = 0.82, P < 0.01). Positive illness cognition had a mediating effect between experiential avoidance and QOL (effect size: −0.56), accounting for 87.14% of the total effect. Conclusions: The QOL was low in Chinese patients with breast cancer. Positive illness cognition had a mediating effect between experiential avoidance and QOL. Caregivers should indirectly improve patients' QOL with breast cancer by improving their positive illness cognition levels.